2024
DOI: 10.1111/apt.17919
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐analysis: Risk of pancreatic cancer in patients with inflammatory bowel disease

Mohammad Zamani,
Shaghayegh Alizadeh‐Tabari,
Mohammad Hassan Murad
et al.

Abstract: SummaryBackgroundStudies exploring the association between inflammatory bowel disease (IBD) and pancreatic cancer have reported inconsistent results.AimsTo provide a comprehensive overview of the risk of pancreatic cancer development in patients with IBD.MethodsWe searched Embase, PubMed, Scopus and ProQuest from inception to 31 October 2023. We included population‐based cohort studies examining the risk of incident pancreatic cancer in adult patients with IBD compared to the non‐IBD population. We also retrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 47 publications
0
0
0
Order By: Relevance
“…IBD may also be associated with metabolic conditions and can often develop extraintestinal manifestations, with an impact on different organs, such as the liver. For instance, it has recently been shown that non-alcoholic fatty liver disease was observed in IBD patients, with a two times higher risk compared to healthy subjects [3].…”
Section: Introductionmentioning
confidence: 99%
“…IBD may also be associated with metabolic conditions and can often develop extraintestinal manifestations, with an impact on different organs, such as the liver. For instance, it has recently been shown that non-alcoholic fatty liver disease was observed in IBD patients, with a two times higher risk compared to healthy subjects [3].…”
Section: Introductionmentioning
confidence: 99%